P147 Use of a connected inhaler system in the pre-biologic assessment of patients with severe asthma. (11th November 2022) - Holmes, J; Dennison, P; Jackson, DJ; D'Ancona, G; Mansur, A; Patel, PH; Pfeffer, P; Chen, C; Shaw, D; Health, Propeller; Heaney, LG
Abstract : Background: Sub-optimal adherence is a significant factor in patients with difficult-to-treat asthma. Aligning adherence to maintenance inhaled corticosteroid (ICS) treatment with digital inhaler monitoring and measuring fractional exhaled nitric oxide (FeNO suppression) can differentiate patients with poor adherence from those who require treatment escalation with type-2 biologic therapy. 1 Objectives: To assess the feasibility and utility of monitoring adherence using a digital connected inhaler system (CIS) within the patient pathway as a service evaluation; identifying patients for initiation of biologic therapies in UK specialist severe asthma clinics (n=7). Methods: Using a CIS (Propeller Health) patients completed adherence monitoring/biomarker profiling over 1–3 months as part of a pre-biologic assessment followed by clinical decision (initiate biologic therapy or continue monitoring – figure 1 ). Patients had the following assessments at baseline and follow-up: spirometry, FeNO, peripheral blood eosinophil count and asthma control questionnaire (ACQ-6). Results: To date, 357 patients have been initiated on the CIS with 278 having outcome data at 3 months. In FeNO-high subjects (FeNO≥45 ppb, n=181) median adherence was 91% (IQR 76%, 99%). In patients with positive FeNO suppression 1 (n=98), significant differences were observed in FeNO (p<0.001), blood eosinophil count (p=0.03), FEV1 (% predicted) (p=0.02), FVC (% predicted) (p=0.01) and ACQ-6 score (p=0.02) compared to patients with negative FeNO suppression. At follow-up, the decision to start biologic treatment was made for 20 (24.2%) non-suppressors vs 14 (14.6%) suppressors (p=0.097). FeNO suppressors starting biologic therapy included those still remaining FeNO high (n=5), eosinophilic (n=2) and on maintenance prednisolone (n=1). In FeNO-low subjects (FeNO<45 ppb, n=95), median adherence was 92.5% (IQR 72.5%, 98.3%) with no difference in measurements seen at 3 months, consistent with previous data supporting this 'cut-point' to identify difficult to treat asthma patients with poor ICS adherence. 1 Conclusion: Using a CIS in conjunction with FeNO monitoring is a useful method for assessing adherence to ICS when assessing patient suitability for biologic asthma therapies and to support adherence in routine care. Reference: Heaney et al . (RASP-UK) Am J Respir Crit Care Med 2019; 199 (4):454–464. Please refer to page A214 for declarations of interest related to this abstract.